Positive electrode active material, all-solid-state battery, and method for producing positive electrode active material

By forming a coating film containing oxygen and glass-forming elements on the surface of the active substance particles, adjusting the Li composition ratio and the polymerization degree of phosphoric acid compounds, the problem of increasing battery resistance caused by direct contact between the sulfide solid electrolyte and the active substance particles is solved, and the battery resistance is increased is achieved. The effective reduction of battery resistance and the improvement of ion conductivity are achieved.

CN119181781APending Publication Date: 2024-12-24TOYOTA JIDOSHA KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410796687.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-20
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The direct contact between the sulfide solid electrolyte and the active substance particles leads to an increase in the battery resistance. Although the existing coating film reduces the deterioration of the electrolyte, it may increase the resistance, making it difficult to achieve the desired battery resistance reduction effect.

Method used

The coating film is formed on the surface of active material particles, which contains oxygen and glass forming elements, such as phosphorus and silicon. By adjusting the Li composition ratio, the polymerization degree of phosphoric acid compounds and the introduction of Si, a composite glass network is formed to promote ion conduction, satisfying the A specific element concentration ratio relationship to reduce battery resistance.

Benefits of technology

By adjusting the composition and structure of the coating film, the battery resistance is significantly reduced, the ion conductivity is improved, and the battery resistance is effectively reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181781A_ABST
    Figure CN119181781A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, an all-solid-state battery, and a method for manufacturing the positive electrode active material. The positive electrode active material includes active material particles and a coating film. The coating film covers at least a portion of the surface of the active material particles. The coating film contains oxygen and a glass-forming element. The glass-forming element contains phosphorus and silicon. The positive electrode active material satisfies the relationship of formula (1) 'CLi / CX < = 2.50' and formula (2) '0 < CSi / CX'. And CLi, CX, and CSi each represent an element concentration measured by X-ray photoelectron spectroscopy. And CLi represents the elemental concentration of lithium. And CX represents the total element concentration of the glass-forming elements. And CSi represents the elemental concentration of silicon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material, an all-solid-state battery, and a method for producing the positive electrode active material. Background Art

[0002] Japanese Patent Application Laid-Open No. 2012-099323 discloses a coating layer including a polyanionic structure. Summary of the invention

[0003] A sulfide-based all-solid-state battery (hereinafter referred to as an "all-solid-state battery") has been developed. An all-solid-state battery contains a sulfide solid electrolyte. In the positive electrode, the active material particles have a high potential. In the positive electrode, if the sulfide solid electrolyte is in direct contact with the active material particles, the sulfide solid electrolyte may deteriorate. Due to the deterioration of the sulfide solid electrolyte (ion conduction path), the battery resistance may increase. Therefore, it is proposed to form a coating on the surface of the active material particles. The coating hinders the direct contact between the active material particles and the sulfide solid electrolyte, thereby reducing the degradation of the sulfide solid electrolyte. However, the coating is also a resistance component. Even if the degradation of the sulfide solid electrolyte is reduced, the desired battery resistance may not be obtained due to the high resistance of the coating.

[0004] The present disclosure is directed to the reduction of battery resistance.

[0005] 1. The positive electrode active material comprises active material particles and a coating. The coating covers at least a portion of the surface of the active material particles. The coating comprises oxygen and a glass-forming element. The glass-forming element comprises phosphorus and silicon. The positive electrode active material satisfies the relationship between the following formulas (1) and (2).

[0006] C Li / C X ≤2.50 (1)

[0007] 0<C Si / C X (2)

[0008] In the above formulas (1) and (2), C Li , C X and C Si They represent the element concentrations measured by X-ray photoelectron spectroscopy. Li Indicates the element concentration of lithium. X Indicates the total element concentration of glass-forming elements. Si Indicates the element concentration of silicon.

[0009] Japanese Patent Publication No. 2012-099323 proposes a coating containing a polyanionic structure. The coating in Japanese Patent Publication No. 2012-099323 is equivalent to the coating film in the present disclosure. The polyanionic structure contains Li3PO4-Li4SiO4. In the examples of Japanese Patent Publication No. 2012-099323, the molar ratio in the coating film is recorded as "Li / P / Si=7 / 1 / 1". It is believed that the Li contained in the coating film is a carrier of ion conduction. According to previous insights, the larger the Li composition ratio, the more expected the reduction in battery resistance.

[0010] However, according to the new findings of the present disclosure, the battery resistance can be significantly reduced by reducing the Li composition ratio to a specific value or less. The left side of the above formula (1) represents the Li composition ratio. Li The element concentration of the like is measured by X-ray photoelectron spectroscopy (XPS). XPS obtains the information of the outermost surface of the measured object (positive electrode active material). That is, it is believed that the Li composition ratio measured by XPS represents the Li composition ratio in the coating film. As shown in the above formula (1), by making the Li composition ratio less than 2.5, it is expected that the battery resistance will be reduced. In addition, it is believed that the Li composition ratio in Japanese Patent Publication No. 2012-099323 is about 3.5.

[0011] Phosphorus (P) is a glass-forming element. That is, P can form oxide glass (glass network) together with oxygen (O). Silicon (Si) is also a glass-forming element. The coexistence of two or more glass-forming elements can form a composite glass network. It is believed that the glass network contains two or more anions (PO4 3- 、SiO4 4- By coexisting two or more anions, the mixed anion effect is expected to be manifested. By utilizing the mixed anion effect, ion conduction is expected to be promoted. In other words, the battery resistance is expected to be reduced.

[0012] 2. The positive electrode active material described in the above “1” may include the following configurations, for example.

[0013] The glass-forming elements further include boron.

[0014] The positive electrode active material further satisfies the relationship of the following formula (3).

[0015] C Si / C X <0.10 (3)

[0016] Boron (B) is also a glass-forming element. By combining P and B, it is expected that the mixed anion effect will be promoted. Si can be a trace amount compared to P and B. For example, P and B form the skeleton of the glass network, and Si can be partially introduced. By introducing a trace amount of Si into the glass network, it is expected that ion conduction will be promoted.

[0017] 3. The all-solid-state battery comprises a positive electrode and a negative electrode. The positive electrode comprises the positive electrode active material described in "1" or "2" above and a sulfide solid electrolyte.

[0018] 4. The method for producing a positive electrode active material includes the following (a) to (c).

[0019] (a) Prepare the coating solution.

[0020] (b) A mixture is prepared by mixing the coating liquid and the active material particles.

[0021] (c) The mixture is dried to produce a positive electrode active material.

[0022] The coating liquid contains a glass-forming material. The glass-forming material contains a condensed phosphoric acid compound and silicon. The condensed phosphoric acid compound contains 83% or more of phosphorus pentoxide, expressed by mass fraction.

[0023] The mass fraction of phosphorus pentoxide (P2O5) in the condensed phosphoric acid compound (hereinafter also referred to as "P2O5 concentration") is an indicator of the degree of polymerization. It is believed that the higher the P2O5 concentration, the higher the degree of polymerization of the condensed phosphoric acid compound. By making the P2O5 concentration 83% or more, it is expected that the battery resistance will be reduced. It is believed that the reason is that the continuity of the glass network in the coating film can be improved.

[0024] 5. The method for producing a positive electrode active material described in the above “4” may include, for example, the following configurations: The above (a) includes the following (a1) and (a2).

[0025] (a1) Synthesizing a condensed phosphoric acid compound by a dehydration condensation reaction of a phosphoric acid compound.

[0026] (a2) Adding silicon to the reaction system of the dehydration condensation reaction.

[0027] By adding Si to the reaction system of the dehydration condensation reaction, Si can be introduced into the phosphoric acid network (condensed phosphoric acid compound). By previously taking Si into the phosphoric acid network, it is expected that the ion conductivity will be improved.

[0028] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present example") are described. However, the present embodiment and the present example do not limit the scope of the technology of the present disclosure. The present embodiment and the present example are illustrative in all aspects. The present embodiment and the present example are non-restrictive. The scope of the technology of the present disclosure includes all variations within the meaning and scope equivalent to the records in the patent claims. For example, it was originally anticipated that any configuration would be extracted from the present embodiment and the present example and that they would be arbitrarily combined.

[0029] The above and other objects, features, aspects and advantages of the present disclosure will become apparent from the following detailed description of the present disclosure in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a conceptual diagram of the positive electrode active material in this embodiment.

[0031] Figure 2 This is a schematic flowchart of the method for producing the positive electrode active material in this embodiment.

[0032] Figure 3 This is a conceptual diagram of the all-solid-state battery in this embodiment.

[0033] Figure 4 The table shows the experimental results.

[0034] Figure 5 It is a graph showing the relationship between Si composition ratio and battery resistance.

[0035] Figure 6 It is a graph showing the relationship between P2O5 concentration and battery resistance. DETAILED DESCRIPTION

[0036] <Explanation of terms>

[0037] “Element concentration (C Li , C X , C Si )" represents the value measured by the following steps. For example, prepare an XPS device manufactured by ULVAC-PHI (product name "PHI X-tool") or its equivalent. Set the positive electrode active material (powder) in the XPS device. Use a pass energy of 224 eV to perform narrow scan analysis. Process the measured data using analytical software. For example, you can use analytical software manufactured by ULVAC-PHI (product name "MulTiPak") or its equivalent. Convert the peak area (integral value) of the Li 1s energy spectrum into the element concentration (C Li ). The peak area of ​​the P2p spectrum is converted into the element concentration of P (C P). Convert the peak area of ​​B1s spectrum into elemental concentration of B (C B ). The peak area of ​​Si2p spectrum is converted into elemental concentration of Si (C Si ). X is the total element concentration of glass-forming elements. For example, when three glass-forming elements, P, B, and Si, are detected, according to the formula “C X =C P +C B +C Si "Find C X .

[0038] The "glass-forming element" can form an oxide glass having a network structure by combining with O. Glass-forming elements may include, for example, P, Si, B, nitrogen (N), sulfur (S), germanium (Ge), and hydrogen (H). The "glass-forming material" refers to a material containing a glass-forming element. The glass-forming material may be any of a simple substance, a compound, or a mixture.

[0039] "P2O5 concentration" means the value measured using the following procedure. Place 0.1 mL of a sample (condensed phosphoric acid compound) and 0.9 mL of distilled water in a plastic test tube. Measure the absorbance at a wavelength of 360 nm. Calculate the P2O5 concentration of the sample from the relationship between the absorbance and the P2O5 concentration (calibration curve).

[0040] Unless otherwise specified, a numerical range such as "m to n%" includes an upper limit and a lower limit. That is, "m to n%" means a numerical range of "m% or more and n% or less". In addition, "m% or more and n% or less" includes "more than m% and less than n%".

[0041] As for the multiple steps, actions, and operations included in various methods, unless otherwise specified, the execution order is not limited to the order of description. For example, multiple steps can be performed simultaneously. For example, the order of multiple steps can also be reversed.

[0042] <Positive electrode active material>

[0043] The positive electrode active material may be composed of one particle. The positive electrode active material may contain two or more particles. That is, the positive electrode active material may be a powder (an aggregate of particles). The positive electrode active material may have a D50 of, for example, 1 to 30 μm, 10 to 20 μm, or 1 to 10 μm. "D50" represents the particle size that accumulates to 50% in the volume-based particle size distribution (cumulative distribution). The particle size distribution can be measured by laser diffraction.

[0044] Figure 1: is a conceptual diagram of the positive electrode active material in this embodiment. The positive electrode active material 5 includes composite particles. The composite particles have a core-shell structure. That is, the positive electrode active material 5 includes active material particles 1 and a coating film 2. The positive electrode active material 5 can be referred to as a "coated active material" or the like.

[0045] <Coating>

[0046] The coating 2 is a shell of the positive electrode active material 5. The coating 2 covers at least a portion of the surface of the active material particle 1. The coverage rate may be, for example, 94% or more. The coverage rate may be, for example, 95% or more, 96% or more, or 97% or more. The coverage rate may be, for example, 100% or less, 97% or less, 96% or less, or 95% or less.

[0047] The "coverage rate" is measured by XPS. XPS is used to measure the element concentration of various elements on the surface of the positive electrode active material. The coverage rate is calculated according to the following formula (4).

[0048] θ=C X / (C X +C Y ) (4)

[0049] In the above formula (4), θ represents the coverage. The coverage is expressed as a percentage (%). X represents the total element concentration of glass-forming elements. For example, when the coating film 2 contains P, B and Si, according to the formula “C X =C P +C B +C Si "Find C X . C Y represents the total element concentration of the constituent elements (excluding Li and O) of the active material particle 1. For example, in the active material particle 1 having "LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2" according to the formula "C Y =C Co +C Ni +C Mn "Find C Y For example, in the case of active material particles having "LiNi 0.8 Co 0.15 Al 0.05 O2" according to the formula "C Y =C Co +C Ni +C Al "Find C Y .

[0050] The thickness of the coating film 2 can be, for example, 5 to 100 nm, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm. The thickness of the coating film 2 can be measured, for example, by cross-sectional observation of the composite particles. Cross-sectional observation can be performed, for example, using a SEM (Scanning Electron Microscope).

[0051] The coating 2 contains O and a glass-forming element (X). The glass-forming element contains P and Si. In addition to P and Si, the glass-forming element may further contain at least one selected from B, N, S, Ge and H. The glass-forming element may contain P, Si and B, for example. The coating 2 may contain, for example, a phosphate skeleton, a silicate skeleton, a borate skeleton, etc. For example, the TOF-SIMS (Time-of-Fl ight Secondary Ion Mass Spectrometry) spectrum of the positive electrode active material 5 may contain PO2 - PO3 - 、SiO3 - 、SiO4 - 、Si2O5 - , BO2 - , BO3 - etc. fragment peaks.

[0052] The coating film 2 may contain Li. In the present embodiment, the relationship of the following formula (1) is satisfied.

[0053] C Li / C X ≤2.50 (1)

[0054] By satisfying the relationship of the above formula (1), it is expected that the battery resistance will be reduced. In addition, it is considered that there are two or more Li sources in the coating film 2. For example, the coating film 2 may contain Li from the Li compound contained in the coating liquid. For example, the coating film 2 may contain Li diffused from the active material particles 1 when the coating film 2 is formed.

[0055] Li composition ratio (C Li / C X ) can be, for example, 2.46 or less, 2.45 or less, 2.42 or less, 2.37 or less, or 1.40 or less. The Li composition ratio can be, for example, 0.1 or more, 0.5 or more, 1.0 or more, 1.40 or more, or 2.00 or more.

[0056] As long as the relationship of the following formula (2) is satisfied, the Si composition ratio is arbitrary.

[0057] 0<C Si / C X (2)

[0058] For example, the relationship of the following formula (3) may be satisfied.

[0059] C Si / C X <0.10 (3)

[0060] Si composition ratio (C Si / C X ) can be, for example, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, or 0.06 or more. The Si composition ratio can be, for example, 0.09 or less, 0.08 or less, 0.07 or less, or 0.06 or less.

[0061] When the coating film 2 contains B, the relationship between the amounts of P and B is arbitrary. For example, "C P / C B =99 / 1~1 / 99", "C P / C B =9 / 1~1 / 9" or "C P / C B =7 / 3~3 / 7”. For example, it can satisfy “1≤C P / C B ” or “2≤C P / C B "And so on.

[0062] <Active material particles>

[0063] The active material particle 1 is the core of the positive electrode active material 5. The active material particle 1 may have a D50 of, for example, 1 to 30 μm, 10 to 20 μm, or 1 to 10 μm. The active material particle 1 may reversibly accommodate Li ions. The active material particle 1 may have any crystal structure. The active material particle 1 may include, for example, a layered rock salt structure.

[0064] The active material particles 1 may have any composition. For example, the active material particles 1 may have a composition represented by the following formula (5).

[0065] Li 1-a Ni x M 1-x O2(5)

[0066] In the above formula (5), the relationship of -0.5≤a≤0.5 and 0<x<1 is satisfied. M is at least one selected from Co, Mn and Al. For example, the relationship of 0.5≤x<1 or 0.6≤x≤0.9 can be satisfied.

[0067] A dopant may be added to the active material particle 1. The dopant may diffuse throughout the particle or may be locally distributed. For example, the dopant may be localized on the particle surface. The dopant may be a substitutional solid solution atom or an intrusive solid solution atom. The amount of dopant added (molar fraction relative to the total amount of the active material particle 1) may be, for example, 0.01 to 5%, 0.1 to 3%, or 0.1 to 1%. The dopant may include, for example, at least one selected from B, C, N, halogen, Si, Na, Mg, Al, Mn, Co, Cr, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Pb, Bi, Sb, Sn, W, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and actinide elements.

[0068] <Method for producing positive electrode active material>

[0069] Figure 2 : is a schematic flow chart of the method for manufacturing the positive electrode active material in the present embodiment. The "method for manufacturing the positive electrode active material in the present embodiment" may be referred to as "the present manufacturing method" hereinafter. The present manufacturing method includes "(a) preparation of a coating liquid", "(b) preparation of a mixture" and "(c) drying". The present manufacturing method may further include, for example, "(d) heat treatment" and the like.

[0070] <(a) Preparation of coating liquid>

[0071] The manufacturing method includes preparing a coating liquid. The coating liquid contains a solute and a solvent. For example, the coating liquid can be formed by dissolving various materials in a solvent. As long as the solvent can dissolve the solute, it can contain any component. The solvent can contain, for example, water, alcohol, etc. The solvent can contain, for example, ion exchange water, methanol, ethanol, etc.

[0072] The amount of the solute may be, for example, 0.1 to 20 parts by mass relative to 100 parts by mass of the solvent. The solute includes a glass-forming material. That is, the coating liquid includes a glass-forming material. The glass-forming material includes a condensed phosphoric acid compound and Si. The glass-forming material may further include a boric acid compound, etc. The solute may further include a Li compound, etc. For example, the coating liquid may be prepared by dissolving a condensed phosphoric acid compound, a Si compound, a Li compound, a boric acid compound, etc. in a solvent.

[0073] The condensed phosphoric acid compound is a P source. The condensed phosphoric acid compound may contain, for example, at least one selected from pyrophosphoric acid, polyphosphoric acid, metaphosphoric acid and phosphoric anhydride. The condensed phosphoric acid compound may be a hydrate, a salt, etc. The condensed phosphoric acid compound has a P2O5 concentration of 83% or more. The P2O5 concentration may be, for example, any one of 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, or 89% or more. The P2O5 concentration may be, for example, any one of 100% or less, 95% or less, 89% or less, or 84% or less.

[0074] <(a1) Dehydration condensation>

[0075] The present manufacturing method may include synthesizing a condensed phosphoric acid compound by a dehydration condensation reaction of a phosphoric acid compound. The phosphoric acid compound (initial raw material) may include, for example, orthophosphoric acid, etc. The phosphoric acid compound may be a hydrate, a salt, etc. The P2O5 concentration of the condensed phosphoric acid compound may be adjusted by the dehydration condensation conditions. For example, the dehydration condensation reaction may be performed by heating the phosphoric acid compound. The heating temperature may be, for example, 400 to 500°C. The heating time may be, for example, any one of 2 to 6 hours, 2 to 4 hours, or 4 to 6 hours.

[0076] <(a2) Si addition>

[0077] The present production method may include adding Si to the reaction system of the dehydration condensation reaction. When the dehydration condensation reaction of the phosphoric acid compound is carried out, Si can be introduced into the condensed phosphoric acid compound by adding Si. By previously taking Si into the phosphoric acid network, it is expected that the ion conductivity will be improved.

[0078] The addition method is arbitrary. For example, a crucible containing Si can be prepared. For example, a crucible made of porcelain can contain Si. The phosphoric acid compound is filled in the crucible. By heating the crucible, a dehydration condensation reaction of the phosphoric acid compound can occur. At the same time, Si can be added to the reaction system by dissolving Si from the crucible. The amount of Si added can be adjusted, for example, by the Si content of the crucible, the heating temperature, the heating time, etc.

[0079] For example, a Si compound (such as SiO2, etc.) can be added to a phosphoric acid compound being heated. The Si compound can be, for example, a powder. For example, a mixture of a phosphoric acid compound and a Si compound can be heated.

[0080] The amount of Si added can be represented by the Si concentration in the condensed phosphoric acid compound. The Si concentration (mass fraction) can be, for example, 600 ppm or more, 708 ppm or more, 1251 ppm or more, 1488 ppm or more, or any one of 2353 ppm or more. The Si concentration can be, for example, 2353 ppm or less, 1488 ppm or less, 1251 ppm or less, or any one of 708 ppm or less. The Si concentration can be measured by ICP emission spectrometry (Inductively Coupled Plasma Atomic Emission Spectroscopy, ICP-AES).

[0081]

[0082] The Li compound is a Li source. In the positive electrode active material 5, as long as the Li composition ratio can be less than 2.5, the solute may contain a Li compound. The Li compound may include, for example, lithium hydroxide, lithium nitrate, lithium carbonate, etc. The timing of adding the Li compound is arbitrary. For example, similarly to Si, the Li compound may be added to the reaction system of the dehydration condensation reaction of the phosphate compound.

[0083] The amount of Li added can be represented by the Li concentration in the condensed phosphate compound. The Li concentration (mass fraction) can be, for example, 1.4% or more, 1.48% or more, 1.6% or more, 1.65% or more, or 1.7% or more. The Li concentration can be, for example, 1.7% or less, 1.65% or less, 1.6% or less, 1.48% or less, or 1.4% or less.

[0084] <Boric acid compounds>

[0085] The boric acid compound is a B source. The boric acid compound may include, for example, orthoboric acid, metaboric acid, tetraboric acid, etc. The boric acid compound may be a hydrate, a salt, etc. The timing of adding the boric acid compound is arbitrary. For example, after dissolving the condensed phosphoric acid compound in a solvent, the boric acid compound may be further dissolved.

[0086] <(b) Preparation of mixture>

[0087] The present manufacturing method includes preparing a mixture by mixing a coating liquid and active material particles 1. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing active material particles 1 (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid in a powder. In the present manufacturing method, any mixing device, granulating device, etc. may be used.

[0088] <(c) Drying>

[0089] The manufacturing method includes manufacturing a positive electrode active material 5 by drying the mixture. The coating film 2 is formed by drying the coating liquid attached to the surface of the active material particle 1. In the manufacturing method, any drying method can be used. For example, the mixture can be dried using a spray dryer. That is, droplets are formed by spraying the suspension from a nozzle. The droplets contain the active material particles 1 and the coating liquid. For example, the positive electrode active material 5 can be formed by drying the droplets using hot air. By using the spray drying method, for example, it is expected that the coverage rate will be improved.

[0090] For example, the positive electrode active material 5 can be produced by using a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(b) preparation of the mixture" and "(c) drying" can be performed substantially simultaneously.

[0091] <(d) Heat treatment>

[0092] The present manufacturing method may include subjecting the positive electrode active material 5 to heat treatment. The coating 2 may be fixed by heat treatment. Heat treatment may also be referred to as "firing". In the present manufacturing method, any heat treatment device may be used. The treatment temperature may be, for example, 150 to 300° C. The treatment time may be, for example, 1 to 10 hours. The heat treatment atmosphere may be, for example, an air atmosphere or an inert atmosphere.

[0093] <All-solid-state battery>

[0094] Figure 3 This is a conceptual diagram of an all-solid-state battery in this embodiment. The battery 100 may have any shape. For example, the battery 100 may have a plate-like shape. The battery 100 includes a power generation element 50. The battery 100 may include an outer package (not shown). The outer package may accommodate the power generation element 50. The outer package may be, for example, a bag made of an Al laminated film. The power generation element 50 includes a positive electrode 10 and a negative electrode 20. The power generation element 50 may further include a separator layer 30. The separator layer 30 is arranged between the positive electrode 10 and the negative electrode 20. The power generation element 50 may have any structure. For example, the power generation element 50 may have either a monopolar structure or a bipolar structure.

[0095] The positive electrode 10 may include, for example, a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector may include, for example, Al foil, etc. The positive electrode active material layer may be disposed on the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material and a sulfide solid electrolyte.

[0096] The amount of the sulfide solid electrolyte to be added may be, for example, 1 to 200 parts by volume relative to 100 parts by volume of the positive electrode active material. The sulfide solid electrolyte may be, for example, any of glass ceramics or argyrodite. The sulfide solid electrolyte may include, for example, Li I-LiBr-Li3PS4, Li2S-SiS2, Li I-Li2S-SiS2, Li I-Li2S-P2S5, Li I-Li2O-Li2S-P2S5, Li I-Li2S-P2O5, Li I-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li 10 GeP2S 12 、Li4P2S6、Li7P3S 11 , Li3PS4, Li7PS6, and Li6PS5X (X=Cl, Br, I).

[0097] For example, "LiI-LiBr-Li3PS4" means a sulfide solid electrolyte generated by mixing LiI, LiBr and Li3PS4 in an arbitrary molar ratio. For example, a sulfide solid electrolyte can be generated by a mechanochemical method. By marking numbers in front of each raw material, the mixing ratio can be limited. For example, "10LiI-15LiBr-75Li3PS4" means that the mixing ratio of the raw materials is "LiI / LiBr / Li3PS4=10 / 15 / 75 (molar ratio)".

[0098] The positive electrode active material layer may further include a conductive material and a binder, for example. The amount of the conductive material and the binder may be, for example, 0.1 to 10 parts by mass, respectively, independently relative to 100 parts by mass of the positive electrode active material. The conductive material may include, for example, acetylene black, vapor grown carbon fiber (VGCF), etc. The binder may include, for example, polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), etc.

[0099] Example

[0100] <Sample>

[0101] Figure 4 TABLE 1 is a table showing the experimental results. Positive electrode active materials and all-solid batteries according to No. 1 to No. 7 were produced as follows.

[0102] No.1

[0103] A coating liquid was prepared by dissolving 10.8 parts by mass of a condensed phosphoric acid compound (manufactured by Rasa Industries, Ltd.) in 166 parts by mass of ion-exchanged water.

[0104] Furthermore, the manufacturing steps of the condensed phosphoric acid compound are as follows. A mixture is prepared by mixing orthophosphoric acid and lithium hydroxide monohydrate. The mass fraction of lithium hydroxide monohydrate in the mixture is 6%. The mixture is placed in a porcelain crucible. The crucible is kept in an electric furnace for 6 hours. The set temperature of the electric furnace is 300° C. The condensed phosphoric acid compound is generated by the dehydration condensation reaction of orthophosphoric acid. Figure 4 In the dehydration condensation conditions, "temperature" indicates the set temperature of the electric furnace (heating temperature), and "time" indicates the holding time (heating time).

[0105] By mixing 50 parts by mass of active material particles (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) was dispersed in 53.7 parts by mass of the coating liquid to prepare a suspension. The positive electrode active material was produced by supplying the suspension to a spray dryer (product name "Mini Spray Dryer B-290", manufactured by BUCHI). The air supply temperature of the spray dryer was 200°C, and the air supply volume was 0.45 m 3 / min. The positive electrode active material was heat treated in air at a temperature of 200°C.

[0106] The positive electrode slurry is prepared by mixing a positive electrode active material, a sulfide solid electrolyte (10Li I-15LiBr-75Li3PS4), a conductive material (VGCF), a binder (SBR) and a dispersion medium (heptane). The mixing ratio of the positive electrode active material and the sulfide solid electrolyte is "positive electrode active material / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material and the binder is 3 parts by mass, respectively, relative to 100 parts by mass of the positive electrode active material. The positive electrode slurry is fully stirred using an ultrasonic homogenizer. A coating is formed by applying the positive electrode slurry to the surface of the positive electrode collector (Al foil). The coating is dried at 100°C for 30 minutes using a hot plate. A positive electrode raw sheet is thus manufactured. A disc-shaped positive electrode is cut out from the positive electrode raw sheet. The area of ​​the positive electrode is 1 cm 2 .

[0107] A negative electrode and a separator layer are prepared. The negative electrode active material is graphite. The same type of sulfide solid electrolyte is used between the positive electrode, the separator layer and the negative electrode. In a cylindrical fixture, the positive electrode, the separator layer and the negative electrode are stacked in sequence to form a laminate. The laminate is pressed to form a power generation element. A terminal is connected to the power generation element to manufacture a fully solid battery.

[0108] No.2~No.6

[0109] like Figure 4As shown, a positive electrode active material and an all-solid-state battery were produced in the same manner as in No. 1 except that the dehydration condensation conditions were changed.

[0110] No.7

[0111] A phosphoric acid solution was prepared by dissolving 10.8 parts by mass of a condensed phosphoric acid compound in 166 parts by mass of ion exchange water. P / C B = 1", a coating solution was prepared by dissolving boric acid (manufactured by Nakalai Tesque Co., Ltd.) in a phosphoric acid solution. A positive electrode active material and an all-solid-state battery were produced in the same manner as in No. 4 except for the above.

[0112] <Evaluation>

[0113] In the condensed phosphoric acid compound, the P2O5 concentration, Li concentration and Si concentration were measured. The Li composition ratio, Si composition ratio and coverage of the positive electrode active material were measured using an XPS device. The resistance of the all-solid-state battery (battery resistance) was measured. The measurement results are shown in Figure 4 .

[0114] <Results>

[0115] Figure 5 It is a graph showing the relationship between Si composition ratio and battery resistance. Figure 5 The results of No. 1 to No. 6 are plotted in the figure. Si / C X ) is larger than 0, it is found that the battery resistance tends to decrease significantly.

[0116] Figure 6 is a graph showing the relationship between P2O5 concentration and battery resistance. Figure 6 The results of No. 1 to No. 6 are plotted in FIG. 1. When the P2O5 concentration is 83% or more, a tendency is found that the battery resistance decreases significantly.

Claims

1. A positive electrode active material comprising active material particles and a coating, wherein the coating covers at least a portion of the surface of the active material particles, the coating comprises oxygen and a glass-forming element, the glass-forming element comprises phosphorus and silicon, and the positive electrode active material satisfies the relationship between formula (1) and formula (2): C Li / C X ≤2.50 (1) 0<C Si / C X (2), In the formula (1) and the formula (2), C Li , C X and C Si represent the element concentrations measured by X-ray photoelectron spectroscopy, C Li Represents the element concentration of lithium, C X represents the total element concentration of the glass-forming elements, and C Si Indicates the element concentration of silicon.

2. The positive electrode active material according to claim 1, wherein The glass-forming element further includes boron, and the positive electrode active material further satisfies the relationship of formula (3): C Si / C X <0.10 (3)。 3. An all-solid-state battery comprising a positive electrode and a negative electrode, wherein the positive electrode comprises the positive electrode active material according to claim 1 or 2, and a sulfide solid electrolyte.

4. A method for producing a positive electrode active material, comprising: (a) preparing a coating solution; (b) preparing a mixture by mixing the coating liquid and active material particles; and (c) drying the mixture to produce a positive electrode active material, The coating liquid contains a glass-forming material, the glass-forming material contains a condensed phosphoric acid compound and silicon, and the condensed phosphoric acid compound contains 83% or more of phosphorus pentoxide, expressed by mass fraction.

5. The method for producing a positive electrode active material according to claim 4, wherein: The method (a) comprises: (a1) synthesizing the condensed phosphoric acid compound by a dehydration condensation reaction of a phosphoric acid compound; and (a2) adding silicon to the reaction system of the dehydration condensation reaction.